Analysis Of The Effect Of Social Media Use On Power Consumption Based Smartphones - Yunita Siagian; Siti Anisah; Solly Aryza (Jurnal Scientia, 2024)
This study analyzes the effect of social media usage on power consumption on web-based smartphones and also explores the difference in power consumption between web-based social media applications and native applications (applications downloaded and installed directly on smartphones). Further analysis will compare the energy efficiency of various types of activities such as scrolling, video streaming, and content uploading. Thus, this study not only provides insight into the effect of social media usage on battery power, but also provides recommendations for users and developers to minimize the impact of power usage on smartphones. The final results are expected to be a reference for improving the design of more energy-efficient applications. The use of social media through web applications can affect the efficiency of battery usage on smartphone devices. This study measures the power consumption patterns of several popular social media platforms and evaluates factors that affect power usage, such as duration of use, interactive activities, and system optimization. The results of the study are expected to provide insight for users to manage power consumption efficiently and for application developers to improve the performance and energy efficiency of their platforms.